Razvijanje literarne zmožnosti pri pouku književnosti - Žbogar, Alenka (Jezik in slovstvo, 2019)
The article provides a definition of literary competence from two of its most important constituent aspects: the reader's perspective, and the aspect of literary texts and their institutionalisation in education. This is followed by an attempt to define literary literacy and reading literacy. The concepts are highlighted from the perspective of various reading surveys and an attempt is made to apply the results to Slovenian school practice.
Keywords: bralna pismenost; bralna zmožnost; bralne raziskave; književnost; literarna pismenost; literarna zmožnost; pouk književnosti